Null genotype of GSTT1 may be associated with esophageal cancer risk: a meta-analysis in Chinese individuals - Liu, Y-P.; Li, L. (Cellular and Molecular Biology, 2017)
Many studies have analyzed the association between between GSTT1 polymorphism and esophageal cancer, however, the results remained inconclusive. We therefore performed an updated meta-analysis based on Chinese individuals. PubMed, Springer Link, Ovid, Chinese Wanfang Data Knowledge Service Platform, Chinese National Knowledge Infrastructure and Chinese Biology Medicine were searched up to December 2016. An OR with the corresponding 95% CI was used to assess the strength of the association. This meta-analysis included 12 studieswith 1246 cases and 1863 controls. Overall, GSTT1 null genotype was associated with an increased esophageal cancer risk when all studies in Chinese populations pooled into this meta-analysis. In stratified studies with geographical location, significantly increased risk was found in North China (OR = 1.45, 95%CI: 1.11–1.91) and in studies with population-based control (OR = 1.29, 95%CI: 1.07–1.55). This study suggested that GSTT1 null genotype may be potential biomarkers for esophageal cancer in China, especially in North China. Studies with larger sample sizes and wider spectrum of populations are warranted to verify this finding.